Kinematic parameters of first and fourth hurdle clearances in female short hurdle race - Nemtsev, O.; Nemtseva, N.; Doludenko, E.; Kucherenko, J.; Chernova, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Top female hurdlers run from the start to the third hurdle with marked acceleration and achieve highest speed at the fourth hurdle or later (Hucklekemkes, 1990). This suggests that the techniques of the hurdle clearance during acceleration and in the top speed phase may differ. However, most of the studies have focused on the parameters of clearance in the phase of high speed (Francis et al., 2004 et al.). Therefore, the aim of this study was to compare kinematic characteristics of the clearance of the first and the forth hurdles. Methods: Five female hurdlers (age 19.8±4.1, height 1.72±0.06 m, weight 62.0±5.8 kg, 100 m hurdles personal best 14.39±0.88 s) took part in the study. Each participant performed one trial of maximal speed running in five-hurdle race using starting blocks. Videotaping was done with two high speed camcorders (240 Hz) placed perpendicular to the run direction, about 20 m away from the first and the forth hurdles. 2D video analysis was carried out with the help of SkillSpector software. Paired sample t-test was used to examine statistical differences of data. Results: Horizontal velocity (HV) of center of gravity (CG) at takeoff before and at touchdown after the first hurdle were significantly smaller than similar parameters at the fourth hurdle (p=0.041 and 0.034). It was also found that the vertical velocity (VV) of CG at takeoff (1.84±0.33 and 1.40±0.21 m/s, p=0.012), the takeoff angle of CG (15.6±3.6 and 11.6±2.7°, p=0.007) and the flight time (0,336±0,028 and 0,327±0,031 s, p=0,032) were significantly larger at the first hurdle clearance. The takeoff distance (1.68±0.11 and 1.90±0.09 m, p=0.001), the takeoff CG height (1.05±0.04 and 1.07±0.04 m, p=0.023) and the stride length (2.86±0.18 and 3.04±0.15 m, p=0.025) were significantly smaller at the first hurdle clearance. Discussion: Thus, hurdlers tend to perform the first hurdle clearance from shorter distance, with a larger takeoff VV and takeoff angle. However, CG maximal height at the first and the forth hurdle clearances is simply possible due to the lower position of CG at the first hurdle takeoff. Faster HV at the forth hurdle clearance allows runners to decrease their flight time and increase the stride length due to takeoff distance. The study results can be used in technical training of hurdlers.